Fecundación de una hembra de Rhodnius prolixus Stal, 1852, por dos machos - Trejos, A. (1966)
Homozygous red-eyed (recessive) females of Rhodnius prolixus (R.O.R. strain) were mated with homozygous red-eyed males, and later with homozygous black-eyed males. The offspring showed that sperm fmm both males is mixed in the female, that the eggs were fertilized by sperm from either male, and that sperm from both males was still capable of fertilizing eight weeks after copulation. These experiments point to serious obstacles to attempts to eradicate Rhodnius prolixus by the release in the natural habitat of males sterilized by radiation.